Quality Assurance in the Hospitality Industry: A Case Study of Capital View Hotel, Koforidua - Turkson, Efua Des-Bordes (2013)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the award of THE COMMONWEALTH EXECUTIVE MASTERS IN BUSINESS ADMINISTRATION (CEMBA) DEGREE,2012